Synthesis and structure of 1′,4′-diphenyl-1a,1′,4′,4′′,5′′,9b-hexahydro-2′′H-dispiro[cyclopropa[l]phenanthrene-1,2′-[1,4]epoxynaphthalene-3′,3′′-thiophene] - Yuewei Wen; Dasan M. Thamattoor (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, C39H30OS, was inadvertently prepared as a Diels–Alder adduct between 1,3-diphenylisobenzofuran and 3-(1a,9b-dihydro-1H-cyclopropa[l]phenanthren-1-ylidene)tetrahydrothiophene. A combination of fused, bridged, and spirocyclic ring systems are all featured within a single molecular structure of this highly crowded polycyclic compound.